Expanding Our Methodological Toolbox: The “Place” of Twitter in the Ethnographic Endeavor - Simonetto, Deana (Qualitative Sociology Review, 2016)
Social media have been increasingly embraced by social actors inhabiting a wide range of social worlds, including the world of professional sports. This paper argues that Twitter has become an indispensible resource for sociologists seeking to better understand these worlds. Using data collected for a study of the Canadian Football League (CFL), the paper contrasts traditional interviews and Twitter as sources of data. This is followed by a discussion of both the unique advantages and limitations of Twitter data in research. The paper ends by encouraging an expansion of sociology’s methodological toolbox to include this form of social media.